Teacher Performance Evaluation at SDN Wawopada Using the Charlotte Danielson Model - Lagale, Theresia Sertika (Universitas Pahlawan Tuanku Tambusai, 2025)
Teacher performance evaluation is essential for improving education quality. This study evaluates teacher performance at SDN Wawopada using the Charlotte Danielson model, which consists of four domains: Planning and Preparation, Classroom Management, Learning Implementation, and Professional Responsibility. The objective is to analyze teacher performance based on these domains and identify areas for improvement. A mixed-method approach combining quantitative and qualitative methods was employed. Data were collected through document studies, observations, questionnaires, and interviews involving 31 respondents, comprising 9 teachers and 22 students. The collected data were analyzed using statistical and descriptive techniques with SPSS version 27 to determine the percentage of scores and categorize teacher performance. The findings indicate that overall teacher performance falls into the